Interviewing as a Vehicle for Theoretical Sampling in Grounded Theory. (9th April 2021) - Foley, Geraldine; Timonen, Virpi; Conlon, Catherine; O'Dare, Catherine Elliott
Interviewing is a frequently deployed data collection method in grounded theory research. Theoretical sampling is a core feature of the grounded theory method. Theoretical sampling is commonly understood as a means for sampling participants with a set of theoretical considerations in mind. However, theoretical sampling also occurs in the actual data generating process, for example through interviewing. Here, we illustrate how interviewing can be used as a vehicle for theoretical sampling. We discuss how to set up an interview study for it to be amenable to theoretical sampling. We show how interviewing and theoretical sampling align as the study proceeds and how interviewing in grounded theory can steer the course for theoretical sampling. We demonstrate how co-construction of data in grounded theory interviewing fuels theoretical sampling. Finally, we show that proceeding with questions for the purpose of theoretical sampling requires reflexivity and flexibility on the part of the researcher. We conclude that generating and analyzing data through the course of interviewing allows the researcher to probe into, expand on, and saturate key concepts and categories which collectively steer the inquiry and subsequent sampling. In the absence of theoretical sampling, it is not possible to grasp the basis for modifying interview questions or to decipher what or how questions should be asked, and for what purpose.